2020
DOI: 10.1186/s13287-020-01929-8
|View full text |Cite
|
Sign up to set email alerts
|

Shedding light on the role of keratinocyte-derived extracellular vesicles on skin-homing cells

Abstract: Extracellular vesicles (EVs) are secretory lipid membranes with the ability to regulate cellular functions by exchanging biological components between different cells. Resident skin cells such as keratinocytes, fibroblasts, melanocytes, and inflammatory cells can secrete different types of EVs depending on their biological state. These vesicles can influence the physiological properties and pathological processes of skin, such as pigmentation, cutaneous immunity, and wound healing. Since keratinocytes constitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 90 publications
0
26
0
Order By: Relevance
“…Therefore, it is likely that keratinocyte-derived lipids or metabolites mediate the observed effect. Extracellular vesicles (EV), secretory lipid bilayer membranes, are key players in the communication between skin-homing cells like keratinocytes and other skin cells [ 19 ]. They contain mRNA, miRNA, low amounts of DNA and numerous proteins and are potentially responsible for the effect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is likely that keratinocyte-derived lipids or metabolites mediate the observed effect. Extracellular vesicles (EV), secretory lipid bilayer membranes, are key players in the communication between skin-homing cells like keratinocytes and other skin cells [ 19 ]. They contain mRNA, miRNA, low amounts of DNA and numerous proteins and are potentially responsible for the effect.…”
Section: Discussionmentioning
confidence: 99%
“…They contain mRNA, miRNA, low amounts of DNA and numerous proteins and are potentially responsible for the effect. Despite the anti-inflammatory activity of keratinocyte exosomes, a subtype of EV, which has been investigated previously, a responsible factor has not yet been identified [ 19 ]. Keratinocyte-derived de novo-synthesized glucocorticoids are also potential candidates that could be responsible for the effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 A number of reviews have also highlighted that EVs secreted by immune or non-immune cells can affect both innate and adaptive immune responses. 13,30,[58][59][60] They can therefore be used as diagnostic and prognostic biomarkers or therapeutic agents in inflammatory skin disorders. 6,55 More specifically, keratinocytes which are the main components of the epidermis, can also release EVs and regulate skin homeostasis, including immune responses and wound healing.…”
Section: Inflammatory Skin Disordersmentioning
confidence: 99%
“…5,11 For instance, keratinocytes which make up 90% of the cells in the epidermis, can communicate with other skin cells such as fibroblasts, melanocytes and immune cells through EVs. 12,13 It was also reported that keratinocyte-EVs can stimulate the expression of metalloproteinase-1 (MMP1) in dermal fibroblasts to modify the ECM. 12 In addition, keratinocyte-EVs and human immortalized keratinocyte (HaCaT)-EVs stimulate fibroblasts migration and induce fibroblast-mediated endothelial tube formation by activating the ERK1/2, JNK, Smad, and p38 signaling pathways, hence mediating wound healing.…”
mentioning
confidence: 99%